Seismic vulnerability assessment and consolidation techniques of ancient masonry buildings: The case study of a Neapolitan Masseria. (August 2022) - Longobardi, Giovanna; Formisano, Antonio
Highlights: Seismic performance of an ancient Neapolitan Masseria has been evaluated. Three analysis types based on the three evaluation levels foreseen by the Italian Guidelines on Cultural Heritage have been applied to the case study building. The analysis results, compared to each other, have shown the problems and the high vulnerability degree of the building. The simplest evaluation level (EL1), compared to the most detailed one (EL3), has provided unconservative results in predicting the building seismic vulnerability. Consolidation interventions have been designed and applied to the structural parts of the Masseria to improve its seismic behaviour. Abstract: In this paper, the seismic vulnerability appraisement, together with repairing and consolidation operations, of a masonry building with cultural and artistic value located in a small city near Naples are reported and discussed. After a brief digression about the condition of historical and cultural Italian heritage damaged by seismic events and usually in poor condition due to a lack of maintenance, the case study is presented and described, providing not only historical news but also information about as-built status, spaces, functions and structural issues. Once the principal failure modes affecting the building are identified, the estimation of seismic vulnerability is performed through three different evaluation levels given by the Italian Guidelines on Cultural Heritage. The analysis results, compared to each other, have shown the problems and the high vulnerability degree of the building. Finally, according to the Italian Guidelines, the consolidation and upgrading interventions are proposed and described to ensure a safety use of the Masseria under seismic actions.